A hybrid novel SVM model for predicting CO2 emissions using Multiobjective Seagull Optimization - Ehteram M.; Sammen S.S.; Panahi F.; Sidek L.M. (Springer Science and Business Media Deutschland GmbH, 2023)
agricultural market; carbon dioxide; carbon emission; Gross Domestic Product; optimization; support vector machine; Iran; carbon dioxide; algorithm; gross national product; Iran; support vector machine; Algorithms; Carbon Dioxide; Gross Domestic Product; Iran; Support Vector Machine